2021
DOI: 10.15406/ipcb.2021.07.00223
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition status of pregnant women in selected internally displaced persons camp in Delta state, Nigeria

Abstract: Introduction: The recent flood situation in Nigeria has contributed to the upsurge in the percentage of Internally Displace Persons particularly in the Delta State. Children and pregnant women are more venerable. Poor Nutritional status internally displaced person is a major occurrence. This has a serious implication for pregnant women in Nigeria. Assessing nutritional status of pregnant women will help in prioritizing need and intervention problems for internally displaced person, therefore this study will as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…19 A widely used method for assessment of weight gain in pregnancy is body mass index (BMI), However, A review of literature between 1995 and 2012 by Médecins sans Frontières confirmed that MUAC is a more acceptable way for diagnosing acute malnutrition in pregnancy because its change is insensitive or has little change with the effect of pregnancy. 20 Also, MUAC easy to measure and may not require the knowledge of gestational age. In humanitarian setting Midupper-arm cir-circumference (MUAC) is more suitable because of its simplicity and may not require knowledge of gestational age or pre-pregnancy weight for diagnosis to be made.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 A widely used method for assessment of weight gain in pregnancy is body mass index (BMI), However, A review of literature between 1995 and 2012 by Médecins sans Frontières confirmed that MUAC is a more acceptable way for diagnosing acute malnutrition in pregnancy because its change is insensitive or has little change with the effect of pregnancy. 20 Also, MUAC easy to measure and may not require the knowledge of gestational age. In humanitarian setting Midupper-arm cir-circumference (MUAC) is more suitable because of its simplicity and may not require knowledge of gestational age or pre-pregnancy weight for diagnosis to be made.…”
Section: Introductionmentioning
confidence: 99%
“…In humanitarian setting Midupper-arm cir-circumference (MUAC) is more suitable because of its simplicity and may not require knowledge of gestational age or pre-pregnancy weight for diagnosis to be made. 20 MUAC has been successful used in several studies for assessment of nutritional status of pregnant women. 8 Although criteria for assessing malnutrition or maternal risk for having low birth weight differs from countries to countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation